PENINGKATAN MINAT DAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) SISWA KELAS II SD N WIROSABAN TAHUN AJARAN 2016/2017 - Yulianti, Dwi Rustinah (Prodi PGSD FKIP Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this research is to determine the enhancement of students’ interest and science learning outcomes of second grade students in SD Negeri Wirosaban Academic Year 2016/2017 through the implementation of cooperative learning model Think Pair Share (TPS). This is a classroom action research (PTK). The students’ interest and science learning outcomes increased in the amount of 14,82%. It can be indicated by the increase of the percentage average of students’ interest based on the questionnaire results for each cycle, for instance in the first cycle, there is an increase from 73,43% to 79,82% in Cycle II. In the pre cycles stage, the percentage of completeness is 35,71% or 10 completed students. Once given a cycle action, the percentage of science mastery increases to 60,71% or 17 completed students. Then in cycle two, there is an increased to 100% or all students experience mastery with an average value of 84,46.